21.1: Invited Paper: High Throughput MOTFT with Organic Etch‐Stopper and SiNx Gate Insulator. Issue 1 (June 2015) - Yu, Gang; Shieh, Chan‐Long; Xiao, Tian; Lee, Karman; Foong, Fatt; Wang, Guangming; Musolf, Juergen; Chen, Zhao; Chang, Frankie; Ottosson, Kristoffer; Park, Jung‐Woo; Chen, Jason; et al.
Abstract : Metal‐oxide TFT (MOTFT) is promising for next generation high information content displays for both portable and TV/monitor applications. With current manufacturing capacity established originally for a‐Si TFT, it would be ideal to develop a MOTFT structure and process most compatible with the equipment available on existing a‐Si TFT line with minimal upgrade and corresponding capital investment. With such intention, we have developed bottom‐gate, top‐source/drain MOTFT with photopatternable organic etch‐stopper (ES) with performance meeting product specifications. Backplane with such MOTFT can be made with same mask counts as that with BCE process.